2015
DOI: 10.2298/vsp140328072z
|View full text |Cite
|
Sign up to set email alerts
|

Association between the SMN2 gene copy number and clinical characteristics of patients with spinal muscular atrophy with homozygous deletion of exon 7 of the SMN1 gene

Abstract: In the Serbian patients with SMA, a higher SMN2 gene copy number correlated with less severe disease phenotype. A possible effect of other phenotype modifiers should not be neglected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Two other studies examined the relationship between SMA phenotype and SMN2 copy number but did not report the number of patients with three SMN2 copies in different phenotype groups ( 37 , 47 ). Mendonça and colleagues compared patients who were homozygous for an SMN1 deletion with those who were compound heterozygotes ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other studies examined the relationship between SMA phenotype and SMN2 copy number but did not report the number of patients with three SMN2 copies in different phenotype groups ( 37 , 47 ). Mendonça and colleagues compared patients who were homozygous for an SMN1 deletion with those who were compound heterozygotes ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zarkov and colleagues reported the mean number of SMN2 copies in patients with SMA type II, III, or IV, and found that the mean number of copies was higher in milder phenotypes (mean 3.1 in type II, 3.7 in type III and 4.2 in type IV; p < 0.05) ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene -NAIP (a neuronal apoptosis inhibitor gene, OMIM: 600355), whose deletions of one or more exons in homozygous state occur in 40-70% of patients with SMA type I 6,7 . In patients with deletion of the 7 and 8 exons of the SMN-gene in a homozygous state, a violation in the NAIP gene is detected simultaneously 8,9,10 . The third gene -H4F5 is located next to the SMN gene.…”
Section: Introductionmentioning
confidence: 99%
“…These days, the association between SMN2 gene copy number and clinical phenotype in patients with SMA is well known, and its possible effect as a phenotype modifier is being examined. 10 11 Even though SMN2 produces less of the full length protein transcript than SMN1 , it is known the number of SMN2 copies affects the phenotype of SMA. 12 …”
mentioning
confidence: 99%